2009
DOI: 10.1111/j.1945-5100.2009.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of universal‐stage measurements of planar deformation features in shocked quartz: Implications for statistical significance and representation of results

Abstract: Abstract-The presence of shocked quartz is one of the key lines of evidence for the impact origin of rocks. Crystallographic orientations of planar deformation feature (PDF) sets in shocked quartz have been used to constrain the peak shock pressure that these grains have experienced. So far no systematic and comparative studies of the various orientation measurement methods and their biases are available. Therefore, three shocked-quartz-bearing thin sections from a meta-greywacke clast in breccia, a biotite-gn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
248
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(259 citation statements)
references
References 17 publications
6
248
2
Order By: Relevance
“…To improve the reproducibility of the U-stage measurements we follow the recommendations by Ferrière et al (2009). A histogram of angles between the c-axis and poles to the lamellae in quartz grains from sample SQ(TU08/01), in 5 • bins, was built using the spreadsheet by Huber et al (2011) and it is shown in Fig.…”
Section: Deformation Lamellae In Quartzmentioning
confidence: 99%
“…To improve the reproducibility of the U-stage measurements we follow the recommendations by Ferrière et al (2009). A histogram of angles between the c-axis and poles to the lamellae in quartz grains from sample SQ(TU08/01), in 5 • bins, was built using the spreadsheet by Huber et al (2011) and it is shown in Fig.…”
Section: Deformation Lamellae In Quartzmentioning
confidence: 99%
“…While not representing equivocal shock metamorphic indicators, theses shattered quartzes are similar to those observed in the target rocks of the Libyan Desert glass, which formed via an impact event [38]. Planar fractures occur frequently in shocked quartz, but are not considered a shock diagnostic unless occurring with the associated PDFs [8]. Although the irregular fractures or their inclusions trials in quartz grains are still not supported an impact origin, they occur along with non-planar microdeformation features in impact affected rocks, e.g., at Vredefort [26].…”
Section: Discussionmentioning
confidence: 72%
“…Reinhard 1931; Emmons 1943). The orientation of the optic axis and the poles perpendicular to planes of PDF were measured and plotted in a stereographic Wulff net and then indexed with MillerBravais indices (hkil), using a stereographic projection template, displaying the possible pole orientations of common PDF planes within a 5° envelope of measurement error (e.g., Engelhardt and Bertsch 1969;Stöffler and Langenhorst 1994;Langenhorst 2002;Ferrière et al 2009b). The stereographic projection template used in this study is an updated version from Ferrière et al (2009b) including five additional known orientations.…”
Section: Methodsmentioning
confidence: 99%
“…The orientation of the optic axis and the poles perpendicular to planes of PDF were measured and plotted in a stereographic Wulff net and then indexed with MillerBravais indices (hkil), using a stereographic projection template, displaying the possible pole orientations of common PDF planes within a 5° envelope of measurement error (e.g., Engelhardt and Bertsch 1969;Stöffler and Langenhorst 1994;Langenhorst 2002;Ferrière et al 2009b). The stereographic projection template used in this study is an updated version from Ferrière et al (2009b) including five additional known orientations. Note that, as recommended by Ferrière et al (2009b), all measured orientations that fall into the overlapping zone between {1013} and {1014} have been treated as belonging to {1013} orientations, because the {1014} orientations are not considered to be a major orientation in comparison to {1013}.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation